An interval valued neutrosophic decision-making structure for sustainable supplier selection. (30th November 2021) - Yazdani, Morteza; Ebadi Torkayesh, Ali; Stević, Željko; Chatterjee, Prasenjit; Asgharieh Ahari, Sahand; Doval Hernandez, Violeta
Highlights: Sustainable supplier selection using an Interval Valued Fuzzy Neutrosophic model. The proposed framework is tested in a large dairy company. Consideration of judgmental conflicts, information inaccuracy and uncertainty. Comparative performance analysis for testing the stability of proposed model. Abstract: Evolution of supply chain management (SCM) in recent years has transformed it beyond the simple logic of benefit and economic point of views. One of such key strategic elements in establishing a sustainable and socially responsive SCM is supplier selection and performance assessment. This study brings forward a sustainable supplier evaluation structure under multiple criteria and interval valued fuzzy neutrosophic (IVFN) model. The proposed structure uses CRiteria Importance Through Inter -criteria Correlation (CRITIC) and combined compromised solution (CoCoSo) under IVFN environment for evaluation and selection of suppliers for a dairy company in Iran. Alternative supplier 5 (S5 ) emerges as the best supplier with the highest overall score (1.168). Average Spearman rank correlation coefficient between the proposed model and other well established decision-making models methods is found as 0.9651 which establishes reliability of model outcomes. The estimated zero value of Gini Index indicates that supplier 5 has a constant ranking in all considered methods. This is a practical sustainable supplier selection platform which allows decision makers in procurement and SC industries to select the most suitable supplier in any pre-determined period.